A future workforce of food-system analysts - Ingram, J; Ajates, R; Arnall, A; Blake, L; Borrelli, R; Collier, R; De Frece, A; Häsler, B; Lang, T; Pope, H; Reed, K; Sykes, R; et al. (Springer Nature, 2019)
A programme developed across five UK universities aims to equip graduate professionals with the skills, tools and capabilities to better understand and manage food-system complexity for food security, for the environment and for enterprise.